The effect of marketing strategy on consumer sentiment, price sensitivity, and purchase intention, on national online shopping day: S-O-R model approach - Damar Sumeru; Tengku Ezni Balqiah (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This study examines the relationship between Consumer Sentiment, which is influenced by stimulus variables, namely Online Shopping Atmosphere, which includes Perceived Festival Entertaining (PFE), Perceived Mass Participation (PMP), Promotion Strategy, which contains Perceived Temptation of Price Promotion (PTPP), Perceived Categories Richness of Promotion (PCRP), moderated by Price Sensitivity, and influencing Consumer Purchase Intention at the National Online Shopping Day (Hari Belanja Online Nasional) festival in Indonesia. The population of the study consisted of 437 respondents who filled out an online questionnaire regarding their online shopping experience during National Online Shopping Day. In achieving the objectives of this study, structural equation modeling was used to analyze the data, and SmartPLS was used to examine the variables of stimuli, organisms, and those influencing the response variable, Consumer Purchase Intention. The results of this study determine whether the stimulus factor can affect Consumer Purchase Intention directly or indirectly so that this can be a consideration for e-commerce in Indonesia to create a marketing strategy that is in accordance with current market conditions.